Fossil penguin beaks from the Eocene of Antarctica : new materials from La Meseta Formation - Haidr, Nadia Soledad (2017)
Fil: Haidr, Nadia Soledad. Instituto de Biología de Organismos Marinos. Puerto Madryn; Argentina